2019
DOI: 10.1017/s1368980018003634
|View full text |Cite
|
Sign up to set email alerts
|

Low knowledge of osteoporosis and its risk factors in urban Indian adults from Pune city, India

Abstract: ObjectiveTo assess knowledge of osteoporosis and its risk factors and to explore associations between knowledge and various sociodemographic factors in Indian adults.DesignCross-sectional study. The Revised Osteoporosis Knowledge Test (OKT) was used to assess knowledge of osteoporosis. Four scores (OKT-total, range 0–32; OKT-exercise, range 0–20; OKT-nutrition, range 0–26; OKT-risk factors, range 0–14) were generated by giving 1 point to every correct answer and 0 points for incorrect or ‘not known’ answers.Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
4
2
0
Order By: Relevance
“…In the case of osteoporosis knowledge among TB patients, the results of our study indicate that 54.7 % of total females had good knowledge on osteoporosis than males ( Fig. 1 ), which is consistent with an Indian study where women were reported to had higher knowledge than men [27] . While males had significantly poor knowledge score (OR 3.86, 95 % CI 1.98–7.53), which would be explained by postulating that osteoporosis in men is a relatively unknown topic and has been described rarely.…”
Section: Discussionsupporting
confidence: 90%
“…In the case of osteoporosis knowledge among TB patients, the results of our study indicate that 54.7 % of total females had good knowledge on osteoporosis than males ( Fig. 1 ), which is consistent with an Indian study where women were reported to had higher knowledge than men [27] . While males had significantly poor knowledge score (OR 3.86, 95 % CI 1.98–7.53), which would be explained by postulating that osteoporosis in men is a relatively unknown topic and has been described rarely.…”
Section: Discussionsupporting
confidence: 90%
“…Osteoporosis knowledge levels indicate that a significant portion of participants in the study had inadequate knowledge about osteoporosis, and only 2.1 to 4.6% showed acceptable knowledge levels, with more than 80% correct responses.Similar types of results were reported about osteoporosis knowledge by Palaclous et al, (2009), Doheny et al, (2007), and Kadam et al, (2018)19 . The results indicate that the people falling in the age group of 18-39 have low levels of knowledge about osteoporosis and make up the majority (67%) of the total participants, whereas in a study byKadam et al, (2018), it showed that people over 40 years had low knowledge levels in the majority19 .…”
supporting
confidence: 86%
“…Osteoporosis knowledge levels indicate that a significant portion of participants in the study had inadequate knowledge about osteoporosis, and only 2.1 to 4.6% showed acceptable knowledge levels, with more than 80% correct responses.Similar types of results were reported about osteoporosis knowledge by Palaclous et al, (2009), Doheny et al, (2007), and Kadam et al, (2018)19 . The results indicate that the people falling in the age group of 18-39 have low levels of knowledge about osteoporosis and make up the majority (67%) of the total participants, whereas in a study byKadam et al, (2018), it showed that people over 40 years had low knowledge levels in the majority19 . In our study, both men and women did not show any significance in between level of knowledge of osteoporosis and level of education, whereas in other studies it was shown that there was a level of significance between knowledge of osteoporosis and education like Etemadifir et al, (2013),Shawa et al, (2011), and some other studies like Yeap et al, (2010), and El-Tawab et al,(2015), observed that a higher socioeconomic level of educated and working women was associated with easier and more access to quality health information 20-23 .…”
supporting
confidence: 86%
“…Another study described similar result about the impact of sunshine on osteoporosis incidence [12]. High BMI which shows overweight, or obesity was also found to raise the incidence of the osteoporosis and a similar result about the role of BMI in the development of osteoporosis was also observed by another study of India [9].…”
Section: Discussionsupporting
confidence: 64%
“…Socioeconomic factors such as age, gender, education level, and socioeconomic status play their role in the occurrence of osteoporosis [6], [7]. In literature, it has been noted that family history, inactive lifestyles, corticosteroids use, no milk use, no fruits and vegetables use, no intake of calcium supplements, no sunshine exposure, smoking, history of chronic diseases, and high body mass weight all are linked with increased incidence of osteoporosis [1], [8], [9], [10]. Although osteoporosis and its linked risk factors are well studied in many countries, however, in Pakistan, the risk factors of osteoporosis are under-studied and especially in the region where this research has been conducted.…”
Section: Introductionmentioning
confidence: 99%